Factors related to death and prolonged hospital stay in a geriatric ward - Cordeiro,Rafaella Lígia Roque (2016)
OBJECTIVE: To identify factors that can determine hospitalization for a period of more than ten days, and those contributing to the death of elderly inpatients. METHODS: We conducted interviews with patients or primary caregivers and compiled epidemiological data, medication use, functionality prior to hospitalization and the Charlson index. We included patients admitted to the emergency room and excluded patients who were admitted electively and those from which we did not obtain complete information. Initially, patients were distributed into two groups: one with hospitalization for less than ten days (G < 10) and the other with more than ten days (G > 10). The two groups were compared according to the outcome death. We used χ2 test and the Mann-Whitney U test. RESULTS: We identified 201 patients. In the G < 10 group, we classified 77 patients, 56% women. The average length of stay was 16 days, the average age was 87 years, 46.0% were using up to 4 medications and 47.5% were using over 4 medications. At admission, 37.8% were using psychotropic drugs and 37.3% had delirium, 26.4% progressed to death. Concerning the length of stay, none of the variables showed significant difference. For the outcome death, the variables delirium, Katz scale and the Charlson index were able to identify patients with higher risk. CONCLUSION: The analysed variables did not allow us to identify patients at increased risk of prolonged hospitalization. The presence of Delirium, higher Charlson index values and lower values in the Katz scale showed a positive association with mortality.